Quantitative analysis of a brass alloy using CF-LIBS and a laser ablation time-of-flight mass spectrometer. (20th December 2017) - Ahmed, Nasar; Abdullah, M; Ahmed, Rizwan; Piracha, N K; Baig, M Aslam
Abstract: We present a quantitative analysis of a brass alloy using laser induced breakdown spectroscopy, energy dispersive x-ray spectroscopy (EDX) and laser ablation time-of-flight mass spectrometry (LA-TOF-MS). The emission lines of copper (Cu I) and zinc (Zn I), and the constituent elements of the brass alloy were used to calculate the plasma parameters. The plasma temperature was calculated from the Boltzmann plot as (10 000 ± 1000) K and the electron number density was determined as (2.0 ± 0.5) × 10 17 cm −3 from the Stark-broadened Cu I line as well as using the Saha–Boltzmann equation. The elemental composition was deduced using these techniques: the Boltzmann plot method (70% Cu and 30% Zn), internal reference self-absorption correction (63.36% Cu and 36.64% Zn), EDX (61.75% Cu and 38.25% Zn), and LA-TOF (62% Cu and 38% Zn), whereas, the certified composition is (62% Cu and 38% Zn). It was observed that the internal reference self-absorption correction method yields analytical results comparable to that of EDX and LA-TOF-MS.